Integrated crop management; Vol.2 (FAO, 1999)
The book presents concepts and strategies tobe recommanded when formulating and co-ordinating agricultural development programmes in hilly areas of Central America. All steps in the development process are considered from the initial identification of intervention areas, to the identification of problems, selection of appropriate technologies, planning of activities, farmer organization, farmer training, farmer extension, community-institutional links, credit and incentives, marketing and agroindustrial development.